HISTORICAL ASPECTS AND OVERVIEW OF LEGAL UNDERSTANDING OF AIRSPACE SOVEREIGNTY CONCEPT - Vodolaskova, Kateryna; Holovko, Svitlana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Goal: define different ideas of the concept of "sovereignty in aviation space" and consider the stages of development of the concept of airspace sovereignty in the context of the airspace bordering the territory of the state. Research methods: documentary analysis and synthesis, comparative analysis, cognitive and analytical, as well as methods of systematization and generalizations. Results: the analysis of legal acts of international significance in the field of aviation law, which determined the modern understanding of the concept of sovereignty in airspace, was carried out. Discussion: deep analysis made it possible to determine that the official recognition of airspace sovereignty under international law gave all states the right to establish rules and exercise sovereign control of any power over their sovereign airspace.